Zur Entwicklung der geographischen Hochgebirgsforschung - Uhlig, Harald; Haffner, Willibald; Justus Liebig University Giessen (My University, 1984)
Überblick über die vorherrschenden Forschungsansätze in der Hochgebirgsforschung seit den Anfängen im 19. Jahrhundert, erschienen als Einleitung zur gleichnamigen Sammlung der wesentlichen Beiträge zum Thema in der Reihe "Wege der Forschung".

Overview of the predominant approaches of the research of high mountain areas ("Hochgebirge") since the beginning in the 19th century, initially published as an introduction to a collection of the major contributions to the topic.
The development of geographical research on high mountain areas
Keywords: Hochgebirgsforschung; Humboldt; Troll; Rathjens; ddc:550